Penerapan Manajemen Partisipasi dalam Pelaksanaan Gernas Baku di RA Al-Azhar Bantur - Yuli Rahayu Indriani (Institut Agama Islam Negeri Langsa, 2019)
The reading interest in Indonesia still relatively low, so it is necessary to make it habitual. This habituation can be do early that children can like to reading books. On May 5 2018, Ditjen PAUD dan Dikmas, Direktorat Pembinaan Pendidikan Keluarga, and Kementerian Pendidikan dan Kebudayaan organized Gerakan Nasional Orang Tua Membacakan Buku (Gernas Baku) for children. There are several methods that can be do for this movement, on of which is through the implementation of management participate. The purpose of this study is to describe the implementation of management parcipate in the application of Gernas Baku at RA Al-Azhar Bantur. This study use qualitative and type of case study research. The result of this study showed that in planning, parents took part in the ceremonies and socialization of Gernas Baku. In addition, parents also help in raising funds to buy children’s story books. In the implementation, parents participate in reading books for children, but monitoring and evaluation parents only give advice for school institution. The implementation of monitoring and evaluation is carried out by the institution and if there is particiption, it is discussed wit parents. This result indicate that parental involvement an important role in the implementation of Gernas Baku.